Integration of Cyber Security Policy and Risk Management in the Air Traffic Control System in the Indonesian FIR - Hafidz K. Jati; Surya Tri Saputra; Martha Saulina (International Journal Of Humanities Education and Social Sciences (IJHESS), 2026)
The increasing reliance of air traffic control systems on digital technology poses cyber threats that have the potential to disrupt national aviation safety. The integration of cyber security policies and risk management has become an urgent need to maintain the reliability of the Air Traffic Control (ATC) system in the Indonesian Flight Information Region (FIR). This study aims to examine the synergy between national cyber security policies as regulated in Presidential Regulation Number 47 of 2023 on the National Cyber Security Strategy and the implementation of the Safety Management System (SMS) in accordance with ICAO standards. The method used is a qualitative-descriptive approach through a literature study of regulations, policy documents, and related research findings. The study results indicate that the cybersecurity policy framework has not yet been fully integrated into the aviation safety management system. Inter-agency coordination, human resource readiness, and digital infrastructure modernization are key factors in strengthening cyber resilience. This research recommends the establishment of a dedicated aviation cybersecurity oversight unit, integration of cyber threat databases across agencies, and enhanced training for ATC personnel. Policy integration and risk management not only strengthen digital resilience but also protect passenger lives and the stability of national airspace